An Analysis of the Influence of accounting Professional Code of Ethics, Intellectual Intelligence, and Locus of Control on Students’ Ethical Attitudes - Yuliniar Ayu Putri Priaditami; Anik Yuliati (BIMA Journal (Business, Management, & Accounting Journal), 2026)
ABSTRACT Purpose: This study aims to analyze the influence of professional code of ethics comprehension, intellectual intelligence, and locus of control on the ethical attitudes of accounting students at UPN “Veteran” East Java, Class of 2021. Methodology: A quantitative cross-sectional survey was conducted with 78 students selected via simple random sampling. Data were collected using a five‑point Likert‑scale questionnaire and analyzed with PLS‑SEM in SmartPLS 3.0, including assessments of convergent and discriminant validity, composite reliability, determination coefficient (R²), and hypothesis testing through path coefficients (β), T‑statistics, and p‑values. Results: Findings reveal that ethics comprehension (β = 0.426; T = 3.234; p < 0.05) and locus of control (β = 0.241; T = 2.096; p < 0.05) positively and significantly affect students’ ethical attitudes, whereas intellectual intelligence has no significant effect (β = 0.244; T = 1.821; p > 0.05). Findings: The results underscore that ethical awareness and internal control beliefs are primary drivers of ethical behavior, while cognitive capacity alone is insufficient. Novelty: This study uniquely integrates psychological and cognitive variables within the Indonesian accounting education context. Originality: It contributes a case study focused on 2021 cohort accounting students at UPN “Veteran” East Java.Conclusion: Practical recommendations include strengthening ethics instruction in curricula and implementing programs to enhance students’ locus of control to promote professional integrity. Type of Paper: Research Article